[Rezension von: Němec, Damián, 1960-, Annotated legal documents on Islam in Europe : Czech Republic] - Přibyl, Stanislav 1966-; Němec, Damián 1960-; Hesová, Zora 1974- (2022)
Recenzja wspomnianej książki stworzona przez doc. Stanislav Přibyl.
Keywords: Rezension